Prospects of Biotechnology in Grape Breeding - Mwamahonje, Andekelile; Kilambo, Deusdedit; Mrosso, Leon; Feyissa, Tileye (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
Genetic improvement of grape cultivars to obtain high quality wine and table grape varieties by conventional breeding methods has been difficult and time consuming. The elite grape varieties developed by conventional breeding techniques have less resistance to fungal and bacterial diseases, drought, quality and yield per plant. Breeding programs of grapes are difficult due to lack of true bred from seed and few traits of importance. Though most grapes constitute large number of genes, they have less effect in tolerating biotic and abiotic stresses. Genetic improvement of grapevine (Vitis vinifera L.) through application of biotechnological techniques provide new strategies in grape breeding programs based on rapid selection or induction of desired traits by marker assisted breeding, genetic engineering and plant tissue culture. This review paper therefore, aims to discuss biotechnological techniques proposed for improvement of grape breeding.